Pengetahuan Dan Sikap Tentang HIV/AIDS Dan Upaya Pencegahan HIV/AIDS - Solihati; Ida Faridah (Sekolah Tinggi Ilmu Kesehatan Yatsi, 2020)
ABSTRACT HIV / AIDS in adolescents is an important matter to consider, given the many behavioral problems adolescents are increasingly vulnerable to HIV / AIDS. The number of cases among adolescents against HIV / AIDS is caused by ignorance and indifference of adolescents. In Indonesia in 2018 HIV / AIDS was reported as many as 433 (84.2%). To determine the relationship between the level of knowledge about HIV / AIDS with HIV / AIDS prevention efforts in adolescents. The research is a type of quantitative research using a descriptive correlation design, a time approach using cross sectional, sampling techniques using simple random sampling. The sample in this study were 133 respondents. Data analysis used univariate analysis and bivariate analysis. Bivariate analysis using Chi Square test. Based on the Chi Square test there is a relationship between the level of knowledge about HIV / AIDS with HIV / AIDS prevention efforts in adolescents (P-value 0.004 <0.05) and there is a relationship between attitudes about HIV / AIDS with HIV / AIDS prevention efforts in adolescents (P -value 0.001 <0.05). Most respondents are well-informed, have a positive attitude, and take preventative measures. Students are expected to increase their knowledge by reading health books or accessing them through other information media so as to increase understanding of HIV / AIDS. Schools are expected to conduct health education programs or provide health information, one of which is about HIV / AIDS in order to increase knowledge and knowledge for students and facilitate library with more resources related to HIV / AIDS.